Growth and instability of oilseeds in India: GROWTH AND INSTABILITY OF OILSEEDS IN INDIA - B GANDHIMATHY, (Journal of Oilseeds Research, 2022)
Oilseeds are one of the basic necessities of human and industrial life as the edible oils are derived from the oilseeds. This study pertains to explore the growth and instability of oilseeds and extent of changes in the area, production and productivity. Traditionally, Indian cooking method is oil based particularly sesame, groundnut and sunflower. Enhancing production of oilseeds and extraction of oils are essential as it reduces imports from foreign countries. Appropriate latest technologies, minimum support prices, disseminating knowledge about the utilization of technical units, educate the farmers, proper irrigation management on drought prone areas, quality of seeds, also improves the oilseed production.